Pengaruh Kompos Daun Matoa Terhadap Pertumbuhan Dan Hasil Tanaman Petsai (Brassica chinensis L.) Pada Tanah Aluvial / The Effect of Matoa Leaf Compost to Growth and Yield of Chinese Cabbage on Alluvial Soil - rusima rusima; siti hadijah; tatang abdurrahman (Fakultas Pertanian Universitas Tanjungpura, 2018)
The Effect of Matoa Leaf Compost to Growth and Yield of Chinese Cabbage on Alluvial Soil Rusima (1), Siti Hadijah (2), Tatang Abdurrahman (2) (1) Students Faculty of Agriculture and (2) Lecturers Faculty of Agriculture University Tanjungpura Pontianak ABSTRACTThis research aimed to determine the effect of matoa leaf compost to growth and yield of chinese cabbage on alluvial soil. The research at the experimental garden in Faculty of Agriculture University Tanjungpura Pontianak, which taken 1,5 months, it was conducted on the 28th March 2017 to 11th Mei 2017. The research used a completely randomized design (CRD), which consists of a single factor, with six treatments, four replications and three samples of plant. The treatments in the research are: m1 (matoa leaf compost 92 g/polybag), m2 (matoa leaf compost 315 g/polybag), m3 (matoa leaf compost 539 g/polybag), m4 (matoa leaf compost 762 g/polybag), m5 (matoa leaf compost 986 g/polybag), dan m6 (matoa leaf compost 1.210 g/polybag). The variables observed in this research included the total leaf area, leaf chlorophyll, root volume, plant fresh weight, and dry weight of plant. The results showed that the matoa leaf compost treatment gave the same response to variables of root volume, leaf chlorophyll, and dry weight. Matoa leaf compost had a real response to total leaf area and fresh weight, dose 539 g/polybag is an effective dose to increase the growth and yield of chinese cabbage plant on alluvial soil. Keywords: Alluvial, Chinese Cabbage, Matoa Leaf Compost.